Hell'o! - Tan, Michelle Siyi. (2011)
Hell’o! is an reinterpretation of the ten courts of hells in Chinese mythology. It is told through a series of black and white illustration books. Most of us hold surface knowledge that Hell is a one-way abyss where souls plunge into eternal fires, purged of their uncleanliness and sins. This pervasive gory imagery goes beyond instilling fear; it compels the living to not only deter from committing wrongs but also encourages the inculcation of morals.